2022
DOI: 10.3389/fmars.2022.905373
|View full text |Cite
|
Sign up to set email alerts
|

Oyster and Barnacle Recruitment Dynamics on and Near a Natural Reef in China: Implications for Oyster Reef Restoration

Abstract: Oysters and barnacles are dominant inhabitants of natural and restored oyster reefs around the world, and high areal coverage of barnacles at natural or restored reefs commonly decreases substrate accessibility for oyster settlement. The overall understanding of oyster and barnacle recruitment dynamics provides invaluable information on site selection and strategies employed for oyster reef restoration. This study documented the temporal and spatial patterns of oyster and barnacle recruitment on and near the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Furthermore, Seavey et al [79] pointed out that understanding the resilience of oyster reef communities to disturbances is key to developing effective conservation and restoration plans. Jiang et al [17] showed that August was the most favorable window for capturing oyster spat via substratum additions to waters around natural reefs. Hernández et al [18] pointed out that site characteristics, including access to adequate larval supply and elevation, greatly influence restoration success.…”
Section: Hotspots Evolution and Research Frontiers In Oyster Reefmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Seavey et al [79] pointed out that understanding the resilience of oyster reef communities to disturbances is key to developing effective conservation and restoration plans. Jiang et al [17] showed that August was the most favorable window for capturing oyster spat via substratum additions to waters around natural reefs. Hernández et al [18] pointed out that site characteristics, including access to adequate larval supply and elevation, greatly influence restoration success.…”
Section: Hotspots Evolution and Research Frontiers In Oyster Reefmentioning
confidence: 99%
“…The severe degradation and loss of natural oyster reefs, caused by activities such as overharvesting, disease, habitat degradation [13], water pollution and coastal zone development, has been recognized as a global problem since scientists became aware of their important ecological function [1,14]. Due to the diversity and high values of ecosystem goods and services provided by oyster reefs, there has been increasing interest in oyster reef restoration in many regions of the world [15][16][17]. Early attention to oyster reef recovery was mainly in the USA, especially in the Gulf of Mexico and the East Coast.…”
Section: Introductionmentioning
confidence: 99%